2019
DOI: 10.1186/s12302-019-0275-0
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of agricultural ammonia emission abatement options for compliance with European air quality regulations

Abstract: Background: In Europe, ammonia (NH 3) emissions strongly contribute to fine particulate matter (PM2.5) pollution and associated premature human mortality. The National Emission Ceilings Directive 2016/2284/EU has set an obligation for all European Union countries to reduce the NH 3 emissions by 6%, relative to 2005, by 2020. This study aims to assess the costs and benefits of four NH 3 emission abatement options for the compliance of the agricultural sector with the commitments of the European air quality regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 54 publications
(65 reference statements)
1
47
0
Order By: Relevance
“…Data were obtained via the open access database provided by Airparif, the association responsible for air quality monitoring in the Paris region (https://www.airparif.asso.fr/en/telechargement/ telechargement-polluant). Over the studied period (and the investigated pollution events), PM 2.5 and NO 2 averaged concentrations were 12 (28) and 29 (35) µg/m 3 , respectively. The spatial variability of hourly concentrations, calculated as the standard deviation (SD) of the datasets available for 13 stations (Figure S1), led to an average value of 4 (7) and 22 (17) µg/m 3 , respectively.…”
Section: Iasimentioning
confidence: 97%
“…Data were obtained via the open access database provided by Airparif, the association responsible for air quality monitoring in the Paris region (https://www.airparif.asso.fr/en/telechargement/ telechargement-polluant). Over the studied period (and the investigated pollution events), PM 2.5 and NO 2 averaged concentrations were 12 (28) and 29 (35) µg/m 3 , respectively. The spatial variability of hourly concentrations, calculated as the standard deviation (SD) of the datasets available for 13 stations (Figure S1), led to an average value of 4 (7) and 22 (17) µg/m 3 , respectively.…”
Section: Iasimentioning
confidence: 97%
“…Several studies highlighted that the unfavorable geographical context, climate characteristics, and intense anthropogenic activities, such as industry and agriculture, of the Po valley promote a high level of air pollution ( Arvani et al, 2014 ; Diémoz et al, 2019 ; Thunis et al, 2009 ). For example, Giannakis et al (2019) found that the highest PM 2.5 concentration from the agricultural sector in Europe is present in northern Balkan countries and Northern Italy. Similarly, Thunis et al (2019) identified as “hotspots” regions for PM emissions the Po valley and Eastern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…NO3 concentrations are closely correlated with seasonal NH3 emissions suggesting that NH3 availability is the limiting factor controlling NH4 . NO3 prevalence (Giannakis et al, 2019). In the SLOW simulation, coarse NO3 concentrations are of a similar magnitude to fine NO3 concentrations over many industrialised regions.…”
Section: Conclusion and Discussionmentioning
confidence: 74%